Face-Saving Strategies in Leni Robredo’s Post-Election Speech - Maico Demi B. Aperocho; Irene Charr C. Lapiña (CV. Literasi Indonesia, 2022)
The role of language in the recently conducted May 2022 Philippine national elections could not be underestimated. For the presidential candidates, language became very functional in expressing their platform and governmental advocacies for the public. Post-election, language still became purposive when former Vice President Leni Robredo, who was defeated in the presidential elections, delivered her post-election speech and expressed her sentiments regarding her loss in the candidacy. This research analyzes the various face-saving discursive strategies in Robredo’s post-election speech using Brown and Levinson’s (1987) Politeness Theory. The researcher used discourse analysis to shed light on how Robredo used language during her post-election speech at the thanksgiving event dedicated to her supporters. The analysis of the 21-minute video recording of her speech reveals that her strategies involved accepting defeat, throwing indirect mudslinging, showing optimism or positivity, emphasizing progress, and avoiding the mentioning of opponents’ names. The conduct of this research is useful in the analysis of political speeches and in elucidating more understanding of the functionality of language for election purposes.